PENINGKATAN SINTASAN LARVA IKAN KERAPU SUNU (Plectropomus leopardus) MELALUI MANAJEMEN PEMELIHARAAN YANG SESUAI - Daniar Kusumawati; Yasmina Nirmala Asih; Ketut Maha Seti (BERITA BIOLOGI, 2019)
Survival rate of coral trout seed produced from aquaculture was relatively low. In 2015, high mortality was found at the early stage of larval development (<D10), approximately 64.37 % of the total production. There has been no standard management for coral trout (Plectropomus leopardus) larval rearing, which was used to adopt management for grouper (Epinephelus spp.) larval rearing. This study was to apply suitable management for coral trout larval rearing into aimed to decrase mortality at early stage larval development and to increase survival rate. There were two different managements in this study: A. applying the results of previous research of coral trout larval rearing from 2004 to 2015, and B. using standard management for grouper larval rearing. The results showed that management A was more suitable management for coral trout larval rearing compared to management B. Management A resulted in the increasing of survival rate by five times (p=0.0056) and of growth rate at early stage by 1.15 times (p=0.2338) higher than those of management B.